Characterization of methanol extract from Renggak (Amomum dealbatum Roxb) leaves and its application as an anion detector. - Baroud, Najah; Al Idrus, Syarifa Wahidah; Rahmawati, R (Acta Chimica Asiana, 2024)
Renggak (Amomum dealbatum Roxb) shows significant potential as a natural resource with applications in various fields, particularly in environmental sensing. This capability positions Renggak as a promising candidate for developing eco-friendly chemosensors, contributing to improved monitoring of these critical anions in the environment and health. Additionally, its diverse phytochemical profile suggests potential uses in medicinal applications, further enhancing its value as a multifaceted plant. This research focuses on the characterization of the methanol extract from Renggak (Amomum dealbatum Roxb) leaves, and it's potential to detect iodide and phosphate anions. The extraction process involved soaking dried renggak leaves in methanol for 72 hours. Afterwards, the solution was filtered and evaporated, resulting in a paste-like extract. The extract was characterized using FTIR and GC-MS techniques, followed by testing its performance as a chemosensor. The paste extract was dissolved in methanol and mixed with a saturated solution of iodide and phosphate salts for the anion detection test. Then, 3 mL of each anion solution was combined with the extract, and any changes in the solution were observed. FTIR analysis revealed the presence of OH groups and C=O double bonds in the methanol extract. GC-MS analysis identified 20 compounds, with hexadecanoic acid and 9-octadecenoic acid being the most abundant. The extract demonstrated fluorescent properties in the anion detection test, acting as a chemosensor. When exposed to a UV lamp at 250 nm, the solution emitted a green fluorescent glow, indicating the successful detection of anions. These findings suggest that the methanol extract of renggak leaves could serve as an effective fluorescent chemosensor for iodide and phosphate anions.